1997
DOI: 10.1139/g97-052
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploid marker assignment in hexaploid oat with the C genome as a reference for determining remnant homoeology

Abstract: Nullisomic lines of hexaploid oat Avena sativa L. (2n = 6x - 2 = 40, AACCDD) cultivar Sun II were used to assign 134 DNA sequences to 10 chromosome-associated syntenic groups. A limited set of ditelosomic lines allowed localization of subsets of these sequences to six chromosome arms. Advantages of using such aneuploids in mapping are in the assignment of gene families, monomorphic RFLP sequences, and oat linkage groups to chromosomes. The published hexaploid oat RFLP linkage map has 38 linkage groups, 17 more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…These clones were distributed by the Western Regional Research Center, USDA-ARS, Albany, Calif. Clones from the UMN library (Kianian et al 1997) were kindly provided by Dr. Ronald Phillips, University of Minnesota, St. Paul, Minn. Clones from the OG (Goffreda et al 1992) and RZ (Causse et al 1994) libraries were generously provided by Dr. Mark Sorrells and Dr. Susan McCouch, respectively, Cornell University, Ithaca, N.Y. (Table 1).…”
Section: Rflp Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These clones were distributed by the Western Regional Research Center, USDA-ARS, Albany, Calif. Clones from the UMN library (Kianian et al 1997) were kindly provided by Dr. Ronald Phillips, University of Minnesota, St. Paul, Minn. Clones from the OG (Goffreda et al 1992) and RZ (Causse et al 1994) libraries were generously provided by Dr. Mark Sorrells and Dr. Susan McCouch, respectively, Cornell University, Ithaca, N.Y. (Table 1).…”
Section: Rflp Analysismentioning
confidence: 99%
“…Limited synteny was revealed by comparing linkage maps of diploid (A) and hexaploid (A, C and D) oats (O'Donoughue et al 1995;Kremer et al 2001;Portyanko et al 2001). Moreover, the three hexaploid oat genomes were defined as only 'segmentally' homoeologous (Kianian et al 1997). Low colinearity among homoeologous linkage groups should not be surprising, however, since chromosomes within each genome have probably undergone rearrangement during the process of evolution prior to the three genomes combining at the hexaploid level.…”
Section: Introductionmentioning
confidence: 99%
“…Aneuploid analysis also demonstrated that homoeologous loci for both umn145 and og19 occur on (Jellen et al 1993). Fox et al (2001) concluded that chromosome 18 corresponds to LG KO33 based on their evidence with RFLP clone umn202, and cite supporting evidence from Kianian et al (1997) that RFLP locus cdo1428b is also located on chromosome 18 by aneuploid analysis and on KO33 by mapping. Generally, caution is advisable when drawing conclusions based on chromosome or chromosome arm cross-comparisons of many different genotypes, since hexaploid oat is known to carry many translocations, leading to only segmental homology and homoeology (Kianian et al 1997).…”
Section: Discussionmentioning
confidence: 90%
“…Fox et al (2001) concluded that chromosome 18 corresponds to LG KO33 based on their evidence with RFLP clone umn202, and cite supporting evidence from Kianian et al (1997) that RFLP locus cdo1428b is also located on chromosome 18 by aneuploid analysis and on KO33 by mapping. Generally, caution is advisable when drawing conclusions based on chromosome or chromosome arm cross-comparisons of many different genotypes, since hexaploid oat is known to carry many translocations, leading to only segmental homology and homoeology (Kianian et al 1997). However, the Dw6/dw6-related genomic region appears to be relatively stable and aneuploid analysis is consistent with our independent conclusion from RFLP analysis of the NILs that umn145 homoeologous regions can be expected on KOD_36,KOD_33,and KOD_11_41?20?45, and that the Dw6/dw6 locus maps to KOD_33.…”
Section: Discussionmentioning
confidence: 91%
“…Attempts to assign oat linkage groups to specific chromosomes and to identify sets of homoeologous chromosomes and homoeologous chromosome segments have been based on genetic analysis with aneuploids [Kianian et al, 1997;Fox et al, 2001]. However, some of these assignments have not been confirmed by further linkage data [Wight et al, 2003;Tinker et al, 2009].…”
mentioning
confidence: 99%